2021
DOI: 10.3390/nu13051619
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucans as Dietary Supplement to Improve Locomotion and Mitochondrial Respiration in a Model of Duchenne Muscular Dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a severe X-linked neuromuscular childhood disorder that causes progressive muscle weakness and degeneration. A lack of dystrophin in DMD leads to inflammatory response, autophagic dysregulation, and oxidative stress in skeletal muscle fibers that play a key role in the progression of the pathology. β-glucans can modulate immune function by modifying the phagocytic activity of immunocompetent cells, notably macrophages. Mitochondrial function is also involved in an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Supplementary Table S10: Target sequences and primers used to create morpholino cln5 zebrafish model. References [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] are cited in the supplementary materials and methods.…”
mentioning
confidence: 99%
“…Supplementary Table S10: Target sequences and primers used to create morpholino cln5 zebrafish model. References [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] are cited in the supplementary materials and methods.…”
mentioning
confidence: 99%
“…Recently, increasing evidence have indicated that gut microbiome could produce metabolites that influence mitochondrial energy production and mitochondrial biogenesis. β-Glucan as a kind of dietary fiber has been reported with a beneficial effect on mitochondria metabolism. For instance, β-glucan exposure improved the locomotor performances and mitochondrial respiration in a muscular dystrophic model . In another study, aqueous extracts of fermented barley and β-glucan alleviated high-fat diet (HFD)-induced obesity in rats.…”
Section: Dietary Fiber Its Derived Metabolites and Mitochondriamentioning
confidence: 97%
“…For instance, β-glucan exposure improved the locomotor performances and mitochondrial respiration in a muscular dystrophic model. 81 In another study, aqueous extracts of fermented barley and β-glucan alleviated high-fat diet (HFD)induced obesity in rats. The authors explained the observed effects by UCP1, thermogenic fat bioenergetics, and mitochondria biosynthesis.…”
Section: Dietary Fiber Its Derived Metabolites Andmentioning
confidence: 99%
“…Muscle birefringence, linked to myofibril organization, was analyzed by placing anesthetized embryos on a glass polarizing filter, covering them with a second polarizing filter, and recording them under a Leica M205FA microscope as described elsewhere [84,85]. Embryos were photographed in a bright field.…”
Section: Birefringence Assaymentioning
confidence: 99%